2009
DOI: 10.1021/ja908441c
|View full text |Cite
|
Sign up to set email alerts
|

Improved Injection in n-Type Organic Transistors with Conjugated Polyelectrolytes

Abstract: To improve injection in n-type organic thin film transistors (OTFTs), a thin conjugated polyelectrolyte (CPE) layer was interposed between electrodes and the semiconductor layer. OTFTs were fabricated with [6,6]-phenyl-C(61) butyric acid methyl ester (PCBM) and Au source and drain contacts. We demonstrate that the insertion of CPEs beneath top-contact Au source/drain electrodes can be a very effective strategy for improving the carrier injection and reducing turn-on threshold voltages of n-channel OTFTs. Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
131
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 28 publications
3
131
0
2
Order By: Relevance
“…[1][2][3] In recent years, CPEs have been extensively studied in the field of organic optoelectronics as they can easily form a uniform thin film via solution processing on top of an emissive layer without suffering an intermixing problem between the two layers. [4][5][6][7][8][9][10] It was reported that the charged nature of CPEs has the ability to enhance polymer light-emitting diode (PLED) efficiencies as a consequence of reduction in the energy barrier for electron injection from high work function metals, much in the same way that charge trapping can, but with greater control and no requirement for pre-stressing. 11 This is understood mainly due to the formation of permanent dipoles at the CPE/metal interface 12,13 as also achieved with dipolar self-assembled monolayers (SAMs), but without their need for specific interface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, CPEs have been extensively studied in the field of organic optoelectronics as they can easily form a uniform thin film via solution processing on top of an emissive layer without suffering an intermixing problem between the two layers. [4][5][6][7][8][9][10] It was reported that the charged nature of CPEs has the ability to enhance polymer light-emitting diode (PLED) efficiencies as a consequence of reduction in the energy barrier for electron injection from high work function metals, much in the same way that charge trapping can, but with greater control and no requirement for pre-stressing. 11 This is understood mainly due to the formation of permanent dipoles at the CPE/metal interface 12,13 as also achieved with dipolar self-assembled monolayers (SAMs), but without their need for specific interface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The IFLs were deposited by simply spin-coating their methanol solutions having a concentration of 0.01% (w/v) (P3TMAHT) and 0.2% (w/v) PF2/6-b-P3TMAHT onto the active layer. The low concentrations were used for minimizing IFL thickness and preventing possible complications due to ion motion and concomitant redistribution of internal electric fields in the device [69]. The incorporation of these novel polyelectrolyte based cathode IFLs resulted in greatly improved PCEs of 6.1% for the P3TMAHT cells and 6.2% for the PF2/6-b-P3TMAHT cells versus the PCE of 5.0% for the control devices without the polymer IFL.…”
Section: Water/alcohol Soluble Conjugated Polymersmentioning
confidence: 99%
“…. 14 2.10 Dependence of the work function of molecule-coated substrates, Φ ORG/SU B , on the workfunction of bare substrates, Φ SU B , for APFO-Green1 [78]. The solid line is added as a guide to the eye, illustrating the slope=1 dependence expected for vacuum level alignment.…”
mentioning
confidence: 99%